Seizing the opportunities of the post-pandemic to save a cultural district: the Bairro Alto case - Costa, P. (International Conference "Grand Projects - Urban Legacies of the Late XX Century"at, 2021)
In several other works we have had the opportunity to discuss the evolution of the Bairro Alto area (and its surrounding areas) in Lisbon, as a cultural district, as well as to study the central factors for the sustainability of creative dynamics in this area of the city. As in several other neighborhoods with similar characteristics around the world, its evolution over the last decades has been marked by profound transformations and the decline of much of the cultural activities and creative dynamics that characterized it, asphyxiated in the face of the processes of massification, gentrification and turistification of the area, which gradually lost the various central functions in a creative neighborhood. At the same time, the erratic and often little-focused nature of planning and public policies in this area, as well as on the entire historical centre of the city, has allowed and even promoted the advancement of these dynamics. The profound social, economic and cultural transformations associated with the health crisis of COVID-19 and the post-pandemic period are now a unique opportunity to rethink the downward trajectory of this neighborhood and consider the possibility of its revitalization as a creative center in the city. Based on a set of interviews with residents and local stakeholders, this text presents a reflection on the potential of the transformations associated with the COVID-19 pandemic period and the post-pandemic evolution for the revitalization of this area of the city, enquiring the role of the various agents and in particular of the public authorities in promoting a more resilient and sustainable solution for the development of this area of the city.